2022
DOI: 10.3390/cells11131987
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Serum Magnesium Concentration in Animal Models of Seizures and Epilepsy—The Effects of Treatment with a GPR39 Agonist and Knockout of the Gpr39 Gene

Abstract: Several ligands have been proposed for the GPR39 receptor, including the element zinc. The relationship between GPR39 and magnesium homeostasis has not yet been examined, nor has such a relationship in the context of seizures/epilepsy. We used samples from mice that were treated with an agonist of the GPR39 receptor (TC-G 1008) and underwent acute seizures (maximal electroshock (MES)- or 6-hertz-induced seizures) or a pentylenetetrazole (PTZ)-induced kindling model of epilepsy. MES seizures and PTZ kindling, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…It binds, however, to the serotonin 5-HT1A receptor [19]. We found non-selective effects of TC-G 1008 on the expression of p-CREB/CREB [16] and TRPM7 [39] proteins in the hippocampus. In the MEST test, we did not exclude the involvement of other targets such as 5-HT1A receptor in the activity of TC-G 1008 [16].…”
Section: Discussionmentioning
confidence: 64%
“…It binds, however, to the serotonin 5-HT1A receptor [19]. We found non-selective effects of TC-G 1008 on the expression of p-CREB/CREB [16] and TRPM7 [39] proteins in the hippocampus. In the MEST test, we did not exclude the involvement of other targets such as 5-HT1A receptor in the activity of TC-G 1008 [16].…”
Section: Discussionmentioning
confidence: 64%
“…GPR39 may also play an important role in magnesium homeostasis. 67 Magnesium homeostasis is associated with epilepsy, and it may have synergistic effects with other antiepileptic agents. 68 , 69 …”
Section: Signaling Pathways Associated With Znr / ...mentioning
confidence: 99%
“…GPR39 may also play an important role in magnesium homeostasis. 67 Magnesium homeostasis is associated with epilepsy, and it may have synergistic effects with other antiepileptic agents. 68,69 As previously mentioned, the activation of KCC2 is closely related to intra-and extracellular chloride regulation and GABAergic inhibition, and the altered electrical activity of hippocampal cells is a key point for seizure suppression.…”
Section: Epilepsy: Gpr39 Exerts Antiepileptic Effects Through Kcc2 An...mentioning
confidence: 99%
See 1 more Smart Citation
“…A 22‐year follow‐up study also revealed that higher oral magnesium supplementation was related to a lower risk of adult epilepsy 12 . Recently, animal research showed a certain relationship between magnesium homeostasis and acute or chronic seizures 13 . Likewise, lower serum calcium concentrations was reported to be associated with a higher risk of epilepsy 9,10,14 .…”
Section: Introductionmentioning
confidence: 96%